2018
DOI: 10.1002/rcm.8058
|View full text |Cite
|
Sign up to set email alerts
|

Development and validation of an assay to analyze atazanavir in human hair via liquid chromatography/tandem mass spectrometry

Abstract: Rationale Assays to quantify antiretrovirals in hair samples are increasingly used to monitor adherence and exposure in both HIV prevention and treatment studies. Atazanavir (ATV) is a protease inhibitor used in combination antiretroviral therapy (ART). We developed and validated a liquid chromatography/tandem mass spectrometry (LC/MS/MS)-based method to quantify ATV in human hair, per the NIH Division of AIDS Clinical Pharmacology Quality Assurance (CPQA) program and the FDA bioanalytical method validation gu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 77 publications
0
11
0
Order By: Relevance
“…This paper examines hair levels as objective markers of antiretroviral adherence among people living with HIV on ART in India for the first time, further exploring the transfer of the hair testing methodology to an India-based laboratory. We found moderate (higher for efavirenz) levels of agreement and correlation between the hair ARV concentrations measured in the India-based laboratory to those measured in the U.S.-based laboratory (the UCSF HAL 26 ), whose assays are reviewed by the Clinical Pharmacology and Quality Assurance program. 22 Moreover, as in previous studies, we found that self-reported adherence was not well-correlated with an objective metric of adherence using hair levels.…”
Section: Discussionmentioning
confidence: 74%
“…This paper examines hair levels as objective markers of antiretroviral adherence among people living with HIV on ART in India for the first time, further exploring the transfer of the hair testing methodology to an India-based laboratory. We found moderate (higher for efavirenz) levels of agreement and correlation between the hair ARV concentrations measured in the India-based laboratory to those measured in the U.S.-based laboratory (the UCSF HAL 26 ), whose assays are reviewed by the Clinical Pharmacology and Quality Assurance program. 22 Moreover, as in previous studies, we found that self-reported adherence was not well-correlated with an objective metric of adherence using hair levels.…”
Section: Discussionmentioning
confidence: 74%
“…Blank hair samples were used as a matrix for standards and controls and were acquired from healthy volunteers, who were HIV‐negative and had never taken TDF, TAF, and FTC. Positive control hair samples were acquired from participants living with HIV, who were recruited from the “Shaved Heads Study” from the UCSF HIV clinic (“Ward 86”) at Zuckerberg San Francisco General Hospital 19 . The “Shaved Heads Study” procedures were approved by the UCSF Institutional Review Board (IRB#14‐13687) and all participants provided written informed consent prior to participation.…”
Section: Methodsmentioning
confidence: 99%
“…Positive control hair samples were acquired from participants living with HIV, who were recruited from the "Shaved Heads Study" from the UCSF HIV clinic ("Ward 86") at Zuckerberg San Francisco General Hospital. 19 The "Shaved Heads Study" procedures were approved by the UCSF Institutional Review Board (IRB#14-13687) and all participants provided written informed consent prior to participation. Participants enrolled in the current study were required to be on TDF-or TAF-containing ART for at least 6 months with good adherence as reported by the provider, the participant, and sustained documented virologic suppression (HIV RNA < 40 copies/ml).…”
Section: Hair Samplesmentioning
confidence: 99%
See 1 more Smart Citation
“…For the development of a TFV-specific immunoassay ( Fig. 1 illustrates a schema of immunoassay development) [17] , the UCSF Hair Analytical Laboratory (HAL), with expertise in LC/MS–MS and analyzing ARV concentrations in hair in the context of HIV treatment and prevention [18] , [19] , formed a collaboration with Alere™ Rapid Diagnostics, a company with expertise in developing POC immunoassays [20] , [21] . Scientists from the UCSF HAL and Alere™ scrutinized the molecular structure of TFV to identify unique derivatives with structural distinction from endogenous nucleotides.…”
Section: Methodsmentioning
confidence: 99%